Alterations of Metabolites in the Frontal Cortex and Amygdala Are Associated With Cognitive Impairment in Alcohol Dependent Patients With Aggressive Behavior - Liu, Chang; Tian, Xuefei; Ling, Yang; Xu, Jiabin; Zhou, Xuhui (Frontiers in Psychiatry, 2020)
Background: Alcohol dependence patients (AD) have a high prevalence of aggressive behavior (AB). The frontal cortex and amygdala contains various neurotransmitter systems and plays an important role in AB. AB is also associated with cognitive deficits. However, no study have addressed this association of metabolites in the frontal cortex and amygdala with cognitive deficits in Chinese aggressive behavior-alcohol dependent patients(AB-ADs). Methods: We recruited 80 male AD and 40 male healthy controls and completed the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), the Modified Overt Aggression Scale (MOAS) and the ¹H MRS scans using 3.0T Siemens. The ¹H MRS data were automatically fit with linear combination model for quantification of metabolite levels of n-acetyl-aspartate (NAA), glutamate (Glu), Choline (Cho) and creatine (Cr). Metabolite levels were reported as ratios to Cr. Results: The AB-ADs group scored significantly lower than the non-aggression-alcohol dependent patients (NA-ADs) on these two RBANS subscales (immediate memory and attention function indices) . The AB-ADs group showed a significant reduction in NAA/CR ratio in the left frontal cortex and Cho/Cr ratio in the left amygdala, and elevation in Glu/Cr ratio in bilateral amygdala, compared with NA-ADs group. NAA/Cr ratio in left frontal cortex was positively associated with immediate memory (r=0.60,P<0.05) and Glu/Cr ratio in right amygdala was negatively associated with delayed memory (r=-0.44,P<0.05) in AB-ADs group. Conclusions: Metabolites alterations in the frontal cortex and amygdala may be involved in the the pathophysiology of aggressive behavior in AD and its associated cognitive impairment, especially immediate memory and delayed memory.